Analytical study of the mechanics of scour for three-dimensional jet - Iwagaki, Yuichi, author; Smith, George L., author; Albertson, Maurice L., author; Colorado State University Research Foundation, publisher (Colorado State University. Libraries, 1960)
A theory of scour for a three-dimensional jet impinging on an erodible bed is developed and applied to the analysis of experimental data obtained in the Hydraulic Laboratory, Colorado State University.
CER60GLS9.
Prepared for U.S. Bureau of Public Roads.
Presented at ASCE Hydraulics Conference, Atlanta, Georgia, August 20, 1958.
Keywords: Jets; Hydraulics; Scour (Hydraulic engineering)